Effect of polymerization on the color of resin composites - KORKUT, BORA; YILMAZ ATALI, PINAR; TARÇIN, BİLGE; GÖÇMEN, GÖKHAN (My University, 2022)
©Operative Dentistry, 2022.OBJECTIVES: The initial shade of a resin-based restorative material should be the same as that after polymerization. In this study, the color changes of translucent and opaque composites from nine different brands were assessed after polymerization using a spectrophotometer and cross-polarization (CP) photography. METHODS AND MATERIALS: Thirteen nano-hybrid (Essentia LE, GC Corp; Ceram.x Duo SphereTEC A2E/A2D, Dentsply Sirona; Harmonize A2E/A2D, Kerr Dental; IPS Empress Direct A2E/A2D, Ivoclar Vivadent; Mosaic EN/A2, Ultradent Products; Clearfil Majesty Es-2 A2E/A2D, Kuraray Noritake; Charisma Topaz A2/OL, Kulzer), two supra nano-hybrid (Estelite Asteria NE/A2B; Tokuyama), two nano-filled (Filtek Ultimate A2E/A2D; 3M) light-curing resin composites, and one micro-hybrid (Essentia MD, GC Corp) light-curing resin composite were tested. Disc-shaped specimens (n=5) were prepared using silicone molds (12 × 5 mm) and polymerized from both sides using an LED curing light (Elipar Deepcure S, 3M) at a light intensity of 1470 mW/cm2. Measurements were performed before and 1 day after polymerization using a contact-type dental spectrophotometer (Easy Shade 5, VITA Zahnfabrik, Bad Säckingen, Germany) and a combination of CP photography and Photoshop CC software (Adobe Inc, San Jose, CA, USA). Spectrophotometry and CP photography ΔE* values were calculated; the perceptibility threshold was a ΔE* value of 1.2. VITA spectrophotometry color change scores were also calculated and evaluated. RESULTS: The overall ΔE* values ranged between 0.34 and 12.56. Two-way analysis of variance (ANOVA) showed that color change was associated most strongly with composite brand (p<0.001), followed by shade (p=0.002). Color change (p=0.002) and degree of darkening/lightening (p<0.001) were significantly greater for dentin compared to enamel shades. Clearfil Majesty Es-2 (Kuraray Noritake) showed significant lightening, whereas all other composites showed darkening after polymerization. All composite brands presented perceptible (ΔE*≥1.2) color changes. Estelite Asteria (Tokuyama), Ceram.x Duo SphereTEC (Dentsply Sirona), and Harmonize (Kerr Dental) were considered the most reliable brands regardless of the shade. The spectrophotometry and CP photography methods were positively correlated (p<0.001). Also, CIEDE2000 and CIELCH (also referred to as CIE L*c*h) color systems were positively correlated based on the ΔE* values (p<0.001). CONCLUSIONS: Despite improvements in the chemical composition of, and fillers for, contemporary resin-based composites (RBCs), all tested composite brands showed perceptible color change after polymerization, except for some shades. Under the conditions in this study, it is preferable to polymerize the composite during the trial phase, before identifying the most appropriate shade. CP photography in combination with Photoshop analysis appears to be a reliable and promising approach for color evaluation.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine